2016
DOI: 10.1177/0972150916630847
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Determinants of Work–Life Balance of Women Employees in Information Technology Companies in India

Abstract: This research article identifies certain factors that strongly impact the work-life balance (WLB) of women employees in information technology (IT) companies in India. These factors are related to the challenges and enhancers to the professional and personal lives of 186 women working in various IT companies in India. The study also identifies the impact of social media (SM) in their work lives. Based on an extensive review of the literature, a set of 42 factors relating to WLB is grouped into five constructs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 42 publications
1
39
0
2
Order By: Relevance
“…Consequently, telework contributes to better WLB because it increases autonomy, decreases stress (Dima et al, 2019) and increases availability to tend to personal and family matters (Gálvez et al, 2020;Thulin et al, 2019). In this sense, Bharathi and Mala (2016) identified that working from home has a great impact as a professional enhancer of women's WLB. Similarly, in a qualitative study by Akbari and Hopkins (2019), many respondents stated that telework contributes to WLB.…”
Section: Telework and Work-life Balancementioning
confidence: 99%
“…Consequently, telework contributes to better WLB because it increases autonomy, decreases stress (Dima et al, 2019) and increases availability to tend to personal and family matters (Gálvez et al, 2020;Thulin et al, 2019). In this sense, Bharathi and Mala (2016) identified that working from home has a great impact as a professional enhancer of women's WLB. Similarly, in a qualitative study by Akbari and Hopkins (2019), many respondents stated that telework contributes to WLB.…”
Section: Telework and Work-life Balancementioning
confidence: 99%
“…The purpose of this study is to review the importance of WLB policies and programmes and its impact on organisational outcomes. Despite the availability of substantial evidence on WLB studies in the Indian context (Munn and Chaudhuri, 2016;Bharathi and Mala, 2016;Kar and Misra, 2013;Baral and Bhargava, 2010); there has been scarcity of studies in the Indian literature till date which has comprised all the empirical studies together focussing on organisational outcomes. Moreover, there are piecemeal studies but not a comprehensive place where all the studies are compiled to provide an overall picture of WLB strategies and its impact on overall organisational outcomes.…”
Section: Purpose Statementmentioning
confidence: 99%
“…Almost all the major sectors of the economy were represented where WLB issues are garnering interest from the practitioners. The IT industry was leading with nine articles (Dhar, 2012;Bharathi and Mala, 2016;Aryasri and Babu, 2009;Maran and Usha, 2014;Valk and Srinivasan, 2011;Joseph et al, 2015;Dhar and Dhar, 2010;Narayanan and Savarimuthu, 2015;Padmanabhan and Kumar, 2016), followed by three articles each from the service sector (Mathew and Panchanatham, 2011;Stock et al, 2016;Sinha, 2013) and the banking sector (Khatri and Behl, 2013;Kundnani and Mehta (2015); Wang et al, 2011). The manufacturing sector (Umamaheswari and Krishnan, 2016;Pradhan et al, 2016), law enforcement sector (Singh and Nayak, 2015;Lambert et al, 2017), education sector (Swarnalatha and Rajalakshmi, 2015;Swarnalatha and Rajalakshmi, 2014) and IT/ BPO sector (Ramadoss, 2013;Boyar et al, 2008) each has two articles, followed by one article each from insurance sector (Das and Kushwaha, 2013) and hotel (Peshave and Gujarathi, 2014) sector.…”
Section: Dominant Industry Sectorsmentioning
confidence: 99%
“…Andreassi and Thompson (2007) found that personality traits explain much variance in WFC and WFF than environmental variables. In the Indian context, Bharathi and Mala (2016) observed that the personal factors impact perception of women employees' work-life balance experience more than the professional factors. However, perusal of existing literature substantiates that the relationship between personality and work-family balance is still at the infancy stage.…”
Section: Introductionmentioning
confidence: 99%